Testing the effectiveness of a new type of spacers for local antibiotic therapy - Ildar F. Akhtyamov; Oskar A. Sachenkov; Rashid A. Shafigulin; Alina E. Galyautdinova; Nikita V. Kharin; Igor A. Bespalov; Sergey V. Boychuk (Гений oртопедии)
Introduction The established treatments for purulent infection in the bone and joint involve one- or two‑stage local effect on the biofilm with use of bone cement and an active substance including an antibiotic in addition to systemic therapy. The objective was to evaluate experimental qualitative and quantitative antibiotic release from bone cement introduced into a new type of lattice-structured spacer. Material and methods A new type of lattice-structured implant/spacer manufactured using additive technologies and a comparison sample simulating a traditional reinforced spacer made of bone cement + antibiotic were used. Vancomycin release was measured by spectrophotometry for periods of 30 days. A regression line was used to plot calibration curves based on data obtained from mother solutions. Results An effective profile of antibiotic release from bone cement was obtained in the first days of the experiment, followed by a decrease at the end of the first week and an exit to a uniform plateau. The amount of fixed antibiotic in solutions did not exceed 1 % of the total mass of bone cement and active substance. The amount of antibiotic released from the lattice-structured samples was higher than that in the comparison samples. Discussion Antibiotic release is a superficial process and is not dependent on the total volume of bone cement. A possible increase in the volume of the medicinal composition does not lead to a proportional increase in the amount of the active substance released. The findings showed that the antibiotic release is more intense even with a smaller volume of material in the lattice structures compared to the control samples, which emphasizes the importance of optimizing the geometry and structure of the material to achieve maximum efficiency of the release of active substances. Conclusion The lattice structure of implants quantitatively affects the release of antibiotic from bone cement into the environment.